The Influence of Rubrics and Peer Assessment on Students’ Works via Google Platform - Kusumawati, Anggara Jatu (International Journal Pedagogy of Social Studies, 2019)
Abstract—this study examines how rubrics and peer assessment can be successfully applied in a classroom to maximize learning outcome. Students find obstacles in assessing the quality of their works.  Furthermore, the lecturer is not able to facilitate all students’ working process. Online platform is also used to cut the complex procedure which affects teaching and learning effectiveness. Data were collected through the result score of students’ works and questionnaires which were analyzed using T-Test SPSS software. The students submitted the work twice on the first work submission and the revision. After getting peer assessment, students revised the work and submitted the work. The finding revealed that rubrics and peer assessment help students to maximize their work. There are some significant progress from the two version of works. However, it needs preliminaries process and learning environmental readiness which limit them to be used in wider context.